The Development Higher Order Thinking Skill (Hots) As Questions In Chemistry Study (Solubility And Solubility Product Constant) - Faucut Sarah; Ibnu Khaldun; Abdul Gani (JURNAL PENDIDIKAN SAINS UNIVERSITAS MUHAMMADIYAH SEMARANG, 2021)
The significance of critical thinking as one of the 21st  century skills makes the Indonesian Ministry of  Education  and  Culture  integrate  Higher  Order Thinking  Skill  (HOTS)  in the  latest national curriculum. Students critical thinking skills to working on HOTS assessment are fundamental, especially in learning chemistry lessons. The research purpose is to analyze the quality of HOTS chemistry questions/ assessment and to observe the teachers and students responses to computer-based test instruments developed using Wondershare Quiz Maker Software (WQM). The research method used Research And Development (R & D) Borg & Gall model. The sample was determined by Random Sampling Technique in total 104 students from several high school in Banda Aceh, it is SMAN 4, SMAN 5, SMAN 8 and SMAN 11. The data analysis technique was through calculating the percentage score of the assessment quality and analyzing the question items quantitatively such as validity, reliability, difficulty level of the questions, differential question power tests and distracting question power using proanaltes. The results showed that the quality of HOTS in chemical questions tested (for the solubility subject and the solubility product constant in terms of qualitative analysis of the items) in the validation test gained average score, it is 98.1%, means the items are qualified categories. In terms of quantitative analysis question items, it reached 95% valid and 5% invalid and the reliability test score was 0.740, are in high category. The questions difficulty covers 95% medium and 5% are in difficult level. The questions differential power for each category is 65% good, 30% medium and 5% less. The teachers and students response to the development of the computer-based HOTS test instrument using WQM software was positive and show good result. The teacher response positively on score strongly agreed was 83.3% and agreed 16.7%, while the students response on score strongly agreed was 27.2% and 63.3% agreed. The research conclusion there is significant  students critical thinking skills improved  (in learning the solubility and the solubility product constant chapter) by using HOTS assessment using Wondershare Quiz Maker software.